Morphological and taxonomical analysis of the terrestrial diatom genus Humidophila (Bacillariophyta) on Ile Amsterdam and Ile Saint-Paul (Southern Indian Ocean) - Chattová, Barbora; Lebouvier, Marc; van De Vijver, Bart (Phytotaxa, 2018)
During a survey of the non-marine diatom flora of the volcanic islands, Ile Amsterdam and Ile Saint-Paul (southern Indian Ocean), seven species belonging to the terrestrial diatom genus Humidophila have been recorded. Apart from five previously known taxa (Humidophila contenta, H. crozetikerguelensis, H. gallica, H. brekkaensis, H. vidalii), two taxa could not be identified based on the currently available literature and are described as new to science: Humidophila amsterdamensis sp. nov. and Humidophila rouhaniana sp. nov. Detailed morphological descriptions of these taxa are given based on both light (LM) and scanning electron microscopy (SEM) observations. The morphological features of each taxon have been compared with similar species and notes on their ecology and associated diatom communities have been added.